2015
DOI: 10.1093/bja/aev157
|View full text |Cite
|
Sign up to set email alerts
|

Fentanyl-induced cough is a risk factor for postoperative nausea and vomiting

Abstract: Non-smoking women undergoing gynaecological surgery who develop FIC during induction of anaesthesia have a higher incidence of PONV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…On emergence from anesthesia, cough may protect against aspiration. However, cough can also result in perioperative morbidity, including tachyarrhythmia, arterial hypertension, cardiovascular collapse, and airway complications, [1][2][3][4][5][6][7][8][9] and it may increase intracranial, intraabdominal, and intraocular pressure. 10 An effective technique for preventing cough would be desirable in many situations where patients are at a particular risk.…”
mentioning
confidence: 99%
“…On emergence from anesthesia, cough may protect against aspiration. However, cough can also result in perioperative morbidity, including tachyarrhythmia, arterial hypertension, cardiovascular collapse, and airway complications, [1][2][3][4][5][6][7][8][9] and it may increase intracranial, intraabdominal, and intraocular pressure. 10 An effective technique for preventing cough would be desirable in many situations where patients are at a particular risk.…”
mentioning
confidence: 99%
“…Oshima et al [14] .completed a cohort study from 1311 adult patients, these authors reported that increasing age, cigarette smoking were associated with a decreased risk of fentanyl-induced cough. OIC is a risk factor for postoperative nausea and vomiting, which means young female nonsmoker may decrease the incidence of postoperative nausea and vomiting by reducing the happening of OIC [15] . However, in a randomized, double-blind study, they found no association of age or smoking status on the incidence of cough in any of the groups [15] .…”
Section: Discussionmentioning
confidence: 99%
“…OIC is a risk factor for postoperative nausea and vomiting, which means young female nonsmoker may decrease the incidence of postoperative nausea and vomiting by reducing the happening of OIC [15] . However, in a randomized, double-blind study, they found no association of age or smoking status on the incidence of cough in any of the groups [15] . So the relationship between patients' individual physical conditions and OIC is remain controversial.…”
Section: Discussionmentioning
confidence: 99%
“…FIC is usually benign, but sometimes leads to an undesirable, exaggerated response like bronchospasm, aspiration of gastric contents, difficult ventilation, increased intracranial, intraocular, or intraabdominal pressure, or an increased incidence of postoperative nausea and vomiting [ 6 7 8 9 10 ]. These unwanted adverse effects are very undesirable at induction of anesthesia, preventing smooth and rapid patient recovery without postoperative adverse sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of FIC varies from a mild self-limiting episode to a severe spasmodic life-threatening cough. Adverse consequences are more dangerous in certain populations, such as patients undergoing ophthalmic or neurosurgical procedures [ 6 7 8 9 10 ].…”
Section: Introductionmentioning
confidence: 99%